The needs analysis for the development of the fardu ain mastery module of the indigenous community of Pahang state - Ismail, Halim; Abdul Razak, Fahmi Zaidi; Abdul Rahman, Asmadi; Sahrir, Muhammad Sabri; Mokhtar, Nazatul Akmar; Sh. Othman, Sh. Mohd Firdaus (Academic Inspired Network, 2024)
The Muslim community in Malaysia consists of various ethnicities and races. Some have embraced Islam since birth and inherited Islam from their ancestors, and some embrace Islam as a new relative, including the indigenous community in this country. Each new group of brothers needs a different religious approach and guidance due to cultural factors, language, and level of education. Thus, the question that arises from these issues is to what extent the level of mastery among the community over the Fardu Ain aspect of their daily lives, especially the natives in the state of Pahang. Accordingly, a mastery module on fardu ain among the indigenous community in the State of Pahang needs to be developed. This module will strengthen the teaching and assessment aspects of the indigenous community in Pahang. Therefore, this study analysed the need to build a more systematic Fardu Ain module based on curriculum components, including objectives, teaching activities, assessment activities, and comprehensive teaching materials based on the ADDIE instructional model. This qualitative study has collected data through semi-structured interviews and analysed it thematically using ATLAS. Software. The study's findings have produced several essential research themes that can be used to improve the existing Fardu Ain Module for the indigenous people of the State of Pahang. This finding is also more comprehensive by not involving the aspects of module content alone but also covering the essential components of module development that are integrated and practical in theory and practice.